Human Capital Development in Western Region, Nigeria, 1955-1968 (2016)
This paper discusses sustained approaches, programmes and strategies for human capital development in the defunct Western Region of Nigeria. Three broad approaches were vigorously pursued, namely, education, technical skills development and agriculture. The most enduring legacy was human capital development through the introduction of free education at the primary school level, which for a long period placed the region among the most highly educated people in Africa. A composite system of secondary education, which provided technical and vocational as well as grammar school, was built up. In fact, education consumed a substantial portion of recurrent and capital expenditure. Within the framework of the Six-Year Development Plan, 1962-1968, Farm Settlement Schemes were established in various parts of the Region for young school leavers in order to boost agricultural production and provide employment opportunities. The paper argues that development plans were indispensable to human capital development.